The Relationship Between Financial Literacy, Lifestyle, Locus of Control, and Parental Income tith the Financial Behavior of University Students - Setyawati, Amelia (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the influence of financial literacy, lifestyle, locus of control, and parental income on student financial behavior. The problem raised is the low level of healthy financial behavior among students despite the increasing access to financial information. This study uses a quantitative approach with a descriptive design. A sample of 120 undergraduate students from the Indonesian College of Economics in Malang was selected using proportional stratified random sampling. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The results showed that financial literacy, lifestyle, and locus of control had a significant effect on student financial behavior, while parental income had no significant effect. The coefficient of determination of 0.163 indicated that 16.3% of the variation in financial behavior was explained by the research variables. This study emphasizes the importance of internal factors over family economic factors. The practical implication is the need for financial literacy programs accompanied by lifestyle guidance and strengthening of students' self-control.